2021
DOI: 10.1088/1361-6587/abdcdc
|View full text |Cite
|
Sign up to set email alerts
|

Multimillijoule terahertz radiation from laser interactions with microplasma waveguides

Abstract: When a relativistic, femtosecond laser pulse enters a waveguide, the pulse energy is coupled into waveguide optical modes. The longitudinal laser field effectively accelerates electrons along the axis of the channel, while the asymmetric transverse electromagnetic fields tend to expel fast electrons radially outwards. At the exit of the waveguide, the ∼nC, ∼10 MeV electron bunch converts its energy to a ∼10 mJ terahertz (THz) laser pulse through coherent diffraction radiation. In this paper, we present 3D part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[20] Moreover, Hu et al found that multi-millijoule THz can be generated from micro-plasma waveguides through coherent diffraction radiation. [21] Nowadays, it was found that the plasmonic electrostatic waves can be coupled into electromagnetic modes in many ways. It was proposed by Sheng et al that laser wakefields driven by ultrashort intense laser pulses in longitudinally inhomogeneous plasmas can be converted via linear mode conversion to powerful THz emission with field strength up to a few tens of MV cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[20] Moreover, Hu et al found that multi-millijoule THz can be generated from micro-plasma waveguides through coherent diffraction radiation. [21] Nowadays, it was found that the plasmonic electrostatic waves can be coupled into electromagnetic modes in many ways. It was proposed by Sheng et al that laser wakefields driven by ultrashort intense laser pulses in longitudinally inhomogeneous plasmas can be converted via linear mode conversion to powerful THz emission with field strength up to a few tens of MV cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research has been carried out in order to increase the efficiency of THz radiation, including the research of Hu et al [23], which was conducted in 2021, and the efficiency was reported to be around 6%. The THz efficiency produced by the frequency difference of Hermite Cosh Gaussian lasers in hot electron-collisional plasma was reported to be approximately 0.08 [24].…”
Section: Introductionmentioning
confidence: 99%
“…The saturation of HHG energy is associated with the suppression of surface wave amplitude, which is responsible for harmonics generation and converting the SAM of fundamental light to the OAM of the harmonics [29]. As a high-power laser propagates in a plasma waveguide, it extracts electrons out of channel wall and accelerate them [40,41]. The total charge of such electrons as shown by the red lines in Fig.…”
mentioning
confidence: 99%